Penjenamaan semula penguatkuasaan permit pemindahan bahan batuan melalui inisiatif penguatkuasaan berasaskan inovasi - Mohamed Halmi, Amir Fadli (2019)
The non-compliance of law caused by weak enforceability and enforcement actions has always been the dilemma of enforcer entities worldwide. In the scope of the Perak land administration, the weaknesses in controlling the non-compliance and breach of condition of the Permit to Remove Rock-Material will affect the State Authority in terms of impairment of royalty collection and deficit in both integrity and public trust. Through 2014, the Perak land administration has taken steps to revolutionize the enforcement methods in line with modern enforcement models as an enforcement rebranding strategies regarding Permit to Remove Rock-Material (4C Permit). Through various innovations, multiple achievements and recognitions have been succesfully gained at state and national level. Thus, this study was conducted based on two objectives namely to identify the successful improvements through the implementation of inovations in 4C Permit, and identifying the success factors of the re-branding program for 4C Permit regulatory via the innovation-based enforcement initiative as the second objective. Data collection methodology was carried out through document analysis and semi structured interviews to respondents based on the objectives of the study. Selection of 10 respondents are among those who are directly involved in the rock material transfer industry regulation hierarchy in Perak. Raw data statement during interviews are transcribed and analized using content analysis and domain analysis method. Researcher conclude that there are six major improvements in 4C Permit regulatory based on innovations. Research findings also state that the success factor of innovation-based enforcement initiatives was contributed by three main factors or domains, namely intelligence, punishment and smart enforcement operated at the highest level through maximizing enforcement resources by the agency. This study also proposes Perak?s first Responsive Regulatory Enforcement Model Pyramid for 4C Permit regulatory and several crucial towards the new horizon of smart enforcement in Malaysia.